Effects of anisotropic misfit strains on equilibrium phases and domain structures in (111)-oriented ferroelectric PbTiO3 films. (March 2021) - Guo, X.W.; Zou, M.J.; Wang, Y.J.; Tang, Y.L.; Zhu, Y.L.; Ma, X.L.
Abstract: Advances in high-index-oriented ferroelectric films offer the exciting possibility of utilizing strain engineering to tune the desired properties related to the nanostructures. Previous studies often considered ferroelectric films grown on cubic substrates (isotropic strain), while the effects of anisotropic strains introduced by orthorhombic substrates are still not well understood. In our recent work, we grew (111)-oriented PbTiO3 (PTO) films on orthorhombic GdScO3 substrates and studied the domain structure evolution with film thickness. However, the theoretical understanding is lacking. In this work, the physical mechanism of the formation and evolution of domain structures was clearly revealed from the viewpoint of energy competition. Moreover, through the stereographic projection (SP) analysis of polarization vectors, a wide variety of ferroelectric phases for (111)-oriented PTO films under anisotropic strains were identified, and the misfit strain-misfit strain domain stability diagram was then constructed at room temperature. It was indicated that anisotropic misfit strains not only lead to the separation of ferroelectric domain variants that could co-exist under isotropic strain states for tetragonal-like d and monoclinic ma phases, but also stabilize the monoclinic mb phase. Their representative domain morphologies with separated domain variants under different anisotropic strains were analyzed in detail. These results provide guidance for interpreting and understanding more experimental data as well as the designing of (111)-oriented epitaxial ferroelectrics under anisotropic strains. Graphical abstrast: Image, graphical abstract